2014
DOI: 10.4028/www.scientific.net/amm.675-677.1451
|View full text |Cite
|
Sign up to set email alerts
|

Study on Recovery of Lead-Zinc Tailing Ore by Electrochemical Flotation

Abstract: The tailing in a large lead-zinc-iron-sulfur multi-metallic mine has rich reservation in variety of metallic minerals. It has been difficult to recover because of all kinds of reasons. The challenges faced by lead-zinc ore beneficiation are, low grade and recovery of lead and zinc concentrate for fine disseminated grain size, high oxidation rate and close intergrowth. This paper presents a Pulp Potential Control Flotation by stages technique to improve the flotation performance of the lead-zinc ores. In the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…5 Many domestic and foreign researchers examined the technologies and principles of separating pyrite and arsenopyrite. Flotation is extensively used and can be classified in four types: heating flotation, oxidants, 6 electrochemical oxidation, 7 and inhibitors. 8 The increased processing volumes of As-containing sulfides and stringent quality requirements for concentrates increased the prominence of inhibitors, which can be divided in two categories: inorganic 9 and organic.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many domestic and foreign researchers examined the technologies and principles of separating pyrite and arsenopyrite. Flotation is extensively used and can be classified in four types: heating flotation, oxidants, 6 electrochemical oxidation, 7 and inhibitors. 8 The increased processing volumes of As-containing sulfides and stringent quality requirements for concentrates increased the prominence of inhibitors, which can be divided in two categories: inorganic 9 and organic.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregate continues to be increased as more concrete is consumed all over the world [ 22 , 23 ]. Since stone and sand are non-renewable resources, the traditional ways to produce aggregate is not sustainable [ 24 , 25 ]. Utilizing ore tailings as valuable concrete raw materials is a feasible treating method, which has received increasing attention for the past years [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This experiment proves that arsenite can be effectively separated by potential regulation. Zhou et al [10] conducted a flotation test study on a complex lead-zinc ore in Jing Dong Tailings Company of Fujian province. The result showed that in the electrochemical potential controlling flotation processing, using DDTC as collector, the separation potential range of galena and sphalerite with pyrrhotite can be achieved.…”
Section: Introductionmentioning
confidence: 99%